PENGARUH KEPERCAYAAN, KEAMANAN BERTRANSAKSI DAN PERSEPSI RISIKO TERHADAP MINAT BELI DI TOKO ONLINE (Studi pada Toko Online Lazada) - Nindhi Kurniarum, 15.05.51.0195; Sutejo, Bambang (Students' Journal of Economic and Management, 2019)
The purpose of this study is to test and analyze the effect of trust, transaction security and risk perception on buying interest in online stores. This study uses a survey method with a questionnaire using google form as a data collection tool. The population of this study is internet users who buy at Lazada's online store. The research sampling technique was purposive sampling with the criteria of consumers who bought at Lazada's online store. Data analysis using multiple linear regression. The results showed that trust has a positive and significant effect on buying interest. In addition, transaction security has a positive and significant effect on buying interest and the perception of risk has a negative and insignificant effect on buying interest.